119k views
0 votes
Write the standard form of the equation of the circle shown.

Write the standard form of the equation of the circle shown.-example-1
Write the standard form of the equation of the circle shown.-example-1
Write the standard form of the equation of the circle shown.-example-2
User Val Kornea
by
5.2k points

2 Answers

5 votes

Answer:


(x+2)^2+(y-2)^2} =13

Explanation:

We are given a circle with a center at the point (4, -5) and two points on the circle (-5, 0) and (1, 0).

We know that the standard form of equation of a circle is:


r=√((x_1-x)^2+(y_1-y)^2)

So putting the given values to get the value of radius (r):


r=√((-2-1)^2+(2-0)^2)


r=√(13)

Substituting the value of radius to get the equation of the circle:


√((x+2)^2+(y-2)^2) =√(13)

Taking square on both the sides:


(x+2)^2+(y-2)^2} =13

Therefore, the equation of the given circle is
(x+2)^2+(y-2)^2} =13.

User Gregjhogan
by
5.5k points
4 votes

The stand form of the circle is


(x-h)^(2) + (y-k)^(2) = r^(2)

here (h,k) is the center of the cirlce and (x,y) is the point on the circle.

In our case (h,k) is (-2,2)

so our circle equation is


(x--2)^(2) + (y-2)^(2) = r^(2). ----------- (i)

and we can find our r by finding the distance between center and the point given on the circle. lets say we take (1,0) point given on the circle according to our diagram

Then


r = \sqrt{(-2-1)^(2)+(2-0)^(2)}


r = √(9+4)


r = √(13)


so by putting the values of r in equation (i)


(x--2)^(2) + (y-2)^(2) = √(13) ^(2)


(x+2)^(2) + (y-2)^(2) = 13

Which is our third option.






User Aaron Renoir
by
5.5k points